Ophitoxaemia: Study of Snake Bites in Western Vidarbha Region - Sachin Janbaji Gadge; Chaitanya Shriram Kulkarni; A. K. Pillai (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: Snakebite envenoming is many times fatal. Venomous snake bites can cause huge morbidity and medical problems from trivial hospitalization to death or amputation. They help in maintaining rodents population and thus boon for farmer’s yield. Materials and method: Prospective cross-sectional study was carried out at Government Medical College and Hospital, Akola, Maharashtra for all the cases who were autopsied with snakebite envenomation from May 2022 to April 2024. Total 76 cases of snake bite were brought for autopsy to our tertiary care hospital Observations and results: Most cases were in 41 to 50 years age group whereas tapering on both the extremes. Mostly residence of rural area 63 (82.89%) whereas predominant occupation of the cases was agricultural 49 (64.47%). Site of incidence of snakebite were at𿿿elds 59 (77.63%) followed by residence 13 (17.11%). Rainy season bears the maximum load of snakebite 49 (64.47%) cases. Conclusions: Strong policy for the Anti Snake Venom (ASV) procurement and its inclusion in essential drugs list is the need of the hour.